2018
DOI: 10.3233/jad-180364
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-127-3p as a Potential Biomarker for Differential Diagnosis in Frontotemporal Dementia

Abstract: Given the heterogeneous nature of frontotemporal dementia (FTD), sensitive biomarkers are greatly needed for the accurate diagnosis of this neurodegenerative disorder. Circulating miRNAs have been reported as promising biomarkers for neurodegenerative disorders and processes affecting the central nervous system, especially in aging. The objective of the study was to evaluate if some circulating miRNAs linked with apoptosis (miR-29b-3p, miR-34a-5p, miR-16-5p, miR-17-5p, miR-107, miR-19b-3p, let-7b-5p, miR-26b-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 64 publications
1
43
2
1
Order By: Relevance
“…However, the clinical significance and role of miR‐127‐3p in the osseous metastasis of PCa remains highly unexplored. Previous studies have demonstrated that the dysregulation of miR‐127‐3p is involved in several diseases, such as pituitary oncocytoma, multiple sclerosis, recurrent miscarriage, doxorubicin‐induced cardiotoxicity, frontotemporal dementia, adenovirus‐infected pneumonia, and primary myelofibrosis . For tumors, many studies have indicated that miR‐127‐3p may serve as either a tumor activator or a suppressor depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance and role of miR‐127‐3p in the osseous metastasis of PCa remains highly unexplored. Previous studies have demonstrated that the dysregulation of miR‐127‐3p is involved in several diseases, such as pituitary oncocytoma, multiple sclerosis, recurrent miscarriage, doxorubicin‐induced cardiotoxicity, frontotemporal dementia, adenovirus‐infected pneumonia, and primary myelofibrosis . For tumors, many studies have indicated that miR‐127‐3p may serve as either a tumor activator or a suppressor depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…As a large class of regulatory non-coding RNA molecules, microRNAs (miRNAs) have been considered to be an important post-transcriptional regulator of many biological processes containing cell growth, proliferation, tissue differentiation, embryonic development and apoptosis [11,12]. Moreover, the high stability of miRNAs in blood and tissues has been con rmed, and many circulating miRNAs have been used for non-invasive detection and treatment of many diseases [13,14]. Fu X et al have studied the role of miR-129-5p in obese individuals, and found that miR-129-5p is highly expressed in both obese individuals and animal models, and obesity is known to be the risk factor for the occurrence of NAFLD [15].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value for the identification and validation of such non-coding RNAs is the revelation of novel drug targets for future translational medicine therapeutic approaches. However, since both miRNAs and lncRNAs are also present within circulating and isolated body fluids, these can also act as diagnostic and disease-stratifying biomarkers for dementia through basic liquid biopsies such as blood sampling [ [108] , [109] , [110] , [111] , [112] , [113] ].…”
Section: Discussionmentioning
confidence: 99%